Secrets of the oracle : a history of wisdom from Zeno to Yeats - Shaw, W. David (William David) (University of Toronto Press, 2009)
What is wisdom? Where does it come from? Where can we find it? And what does it mean in our lives?Shaw explores these questions by turning to the works of wisdom writers, whose words retain their meaning and transformative power even centuries after they were written.